Gênero em desafio: das trobairitz provençais às repentistas nordestinas - Luciana Eleonora de Freitas Calado Deplagne (Estudos de Literatura Brasileira Contemporânea)
This article spaeks of the poetics of the oral tradition sung by women during the Middle Ages and in nowadays Northeast Brazil. Thus, we try to identify the dialogue between the matches of women repentistas and the dialogued medieval songs – the tensons of the provençal trobairitz and the satirical verses of the women poets from the Al-andalus. The proximity is due not only in the formal level, but also in the thematic, specially in the gendered debate over these female production.